Study of Process Parameter and Microstructure of Freeze Casting Technology: A Review. Issue 1 (April 2020) - Bhatt, Mohit; Dhama, Nikhil; Kumar, Mohit; Singh, Mithul; Kumar, Sudhir; Singh, Kanwar Pal; Kumar, Arvind; Singh, Vikram
Abstract: Now a day various technologies are used for casting a product and freeze casting is one of them. Freeze casting is the process of casting a product at a lower freezing temperature for getting a porous structure. There are lots of factors that affect the freeze casting process like freezing temperature, freezing agent, slurry, additive, solid loading, freezing velocity, feed pressure etc. In this review paper, we focused the studying effect of this influencing parameter. This review paper highlights the research done by various researchers to optimize the input parameter for getting an economical and good quality of the cast product. An attempt has been made to conclude the effect of the range of process parameters and the comparison of various methods of freeze casting for the sound quality of cast products. In this paper, different freeze casting process parameters and their effect on the mechanical and Microstructural properties of the products are also summarized.